2019
DOI: 10.1111/jcmm.14518
|View full text |Cite|
|
Sign up to set email alerts
|

FSP1 promotes the biofunctions of adventitial fibroblast through the crosstalk among RAGE, JAK2/STAT3 and Wnt3a/β‐catenin signalling pathways

Abstract: Emerging evidence indicates that fibroblast‐specific protein 1 (FSP1) provides vital effects in cell biofunctions. However, whether FSP1 influences the adventitial fibroblast (AF) and vascular remodelling remains unclear. Therefore, we investigated the potential role and action mechanism of FSP1‐mediated AF bioactivity. AFs were cultured and stimulated with FSP1 and siRNA‐FSP1 in vitro. Viability assays demonstrated that siRNA‐FSP1 counteracted AFs proliferative, migratory and adherent abilities enhanced with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…CTNNB1 is generally considered as an intermediate regulator molecule of the FGF19-FGFR4 signaling pathway [ 28 , 36 , 37 , 38 ]. In addition, a lot of studies have shown that the downregulation of CTNNB1 was associated with the downregulations of CDH2, ALCAM and ICAM1, which is consistent with our results [ 31 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The extracellular FGF19-FGFR4 signaling pathway mediates the expression of cell adhesion molecules and regulates specific tumorigenic events, including cancer cell proliferation and metastasis, by activating the expression of downstream intracellular genes [ 35 , 49 , 50 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…CTNNB1 is generally considered as an intermediate regulator molecule of the FGF19-FGFR4 signaling pathway [ 28 , 36 , 37 , 38 ]. In addition, a lot of studies have shown that the downregulation of CTNNB1 was associated with the downregulations of CDH2, ALCAM and ICAM1, which is consistent with our results [ 31 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The extracellular FGF19-FGFR4 signaling pathway mediates the expression of cell adhesion molecules and regulates specific tumorigenic events, including cancer cell proliferation and metastasis, by activating the expression of downstream intracellular genes [ 35 , 49 , 50 ].…”
Section: Resultssupporting
confidence: 93%
“…Studies have shown that the FGF19-FGFR4 signaling pathway was an effective antitumor target via mediating a lot of intracellular molecules [ 52 , 53 ]. CTNNB1 as an intermediate molecule between the FGF19-FGF4 signaling pathway and adhesion molecules such as ICAM1, CDH2 and ALCAM [ 31 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 58 ] was downregulated after EPS364 treatment. Hence, we speculated that EPS364 might target the FGF19-FGF4 signaling pathway to regulate the expression of adhesion molecules.…”
Section: Discussionmentioning
confidence: 99%
“…TEM is an important method for the characterization of autophagosomes as it can directly visualize their inner architecture. The procedure was performed as previously described (Fu et al, 2019). In brief, the cells were washed with PBS and resuspended, and then post-fixed by 2% OsO 4 (Electron Microscopy Sciences), dehydrated with different concentrations of alcohol and acetone, and then embedded in epoxy resin.…”
Section: Transmission Electron Microscope (Tem)mentioning
confidence: 99%
“…In accordance with our findings, previous studies indicated that anticancer agents inhibited tumor growth, induced autophagy, and suppressed the JAK2/STAT3 pathway, while the autophagy inhibitor CQ enhanced this effect [42][43][44][45]; however, the mechanisms remain unclear, because the RAGE and STAT3 pathways are also regulated by various factors, including HMGB1, NF-κB, fibroblast-specific protein 1 (FSP1), SOCS3, CXCR3, etc. [46][47][48][49][50]. This could partially explain how PT combined with CQ might affect a complicated network in cells when regulating the RAGE and STAT3 pathways.…”
Section: Discussionmentioning
confidence: 99%